Getting to 'no': Three ways to jointly accomplish an answer to questions in a questionnaire in doctor–patient interaction. (26th November 2018) - Andersen, Elisabeth; Rasmussen, Gitte; Brouwer, Catherine; Isaksen, Jytte
Abstract : This paper aims to describe the interactional processes through which a medical professional and a patient collaboratively accomplish filling out answers to a questionnaire. Empirical analysis of three different sequences from a video-recorded doctor-patient interaction in which questions of a questionnaire were answered with a 'no' reveals three different ways (or methods) in which doctor and patient accomplish this jointly. Applying ethnomethodological conversation analysis (EMCA) as our methodological framework, we conclude that the three interactional practices are fitted in relation to the constraints of the interview that is itself methodically aligned to the practices and organizational structures of the institution, a Danish hospital. Furthermore, we make the case that questionnaires are designed as idealizations of question-answer sequences, and as such do not operate at the same level of detail as the actual question-answer situation. Details that are crucial for the objective of the questionnaire (in this case providing information to a third party) may not be included in the recorded answer. Thus, we argue that in order to understand the informational value of recorded answers in questionnaires, we need to diagnose the interaction in which they were produced, i.e. to critically examine it.